Evaluation Of Polypharmacy And Excessive Polypharmacy In Geriatric Inpatients In General Hospital - Surya Lita, Erlinda; Paulina Sormin, Ida (Jurnal Health Sains, 2024)
Polypharmacy is the simultaneous use of drugs with 5-9 drugs. Excessive polypharmacy is the simultaneous use of drugs with ≥ 10 drugs. Chronic diseases that are commonly suffered by geriatric patients are prone to causing a person to receive polypharmacy or excessive polypharmacy. This study aims to eval_uate polypharmacy and excessive polypharmacy in inpatient geriatric patients, by knowing the factors that may trigger a person to receive polypharmacy. The research uses a cross-sectional study method, using medical record data for the period January to December 2023. The part studied was in the form of sociodemographics, disease history and treatment of patients, as well as length of stay. From the research conducted, the results were obtained from 295 patient data samples with 141 patients (47.8%) and 154 patients (52.5%) were female. The age of patients consisted of 60-74 years old 192 patients (65.1%), 75-90 years old 100 patients (33.9%), and ≥ 90 years 3 patients (1%). The last education of the highest patient with a high school background was 101 patients (34.2%), the highest marital status was married as many as 245 patients (83.1%). The diagnosis of the third disease has the most patients, namely diabetes mellitus as many as 95 patients (15.5%), anemia as many as 70 patients (11.5%), and hypertension as many as 56 patients (9.2%). The preval_ence of polypharmacy in geriatric patients was 115 patients (39%) and excessive polypharmacy was 180 patients (61%). Broadly speaking, the sociodemographics of patients do not have a relationship with the occurrence of polypharmacy and excessive polypharmacy. The patient's clinical condition has a relationship with the occurrence of polypharmacy and excessive polypharmacy, this is evidenced by a p value of 0.000 (<0.05). The length of hospitalization and diagnosis of the patient's disease is a predictor of polypharmacy and excessive polypharmacy.